Technological progress bias and its impact on resource efficiency in China’s mariculture industry - Kong, Jiaojiao; Sun, Yanan (Frontiers in Marine Science, 2025)
Technological progress (TC) is an important driving force of resource efficiency, and its bias has an important impact on resource efficiency. Based on the data of China’s mariculture industry from 2008 to 2020, this paper constructs a double-layer nested CES production function, and uses the seemingly unrelated regression method to estimate the elasticity of substitution between resource elements and non-resource elements of mariculture industry, and measures the level of resource biased technological progress (RBTC). On this basis, the vector autoregressive model is used to explore the relationship between RBTC, resource price and resource efficiency. The results show that: Firstly, there is complementarity between the resource elements of China’s mariculture industry and the non-resource elements aggregated by labor and capital. Secondly, there is a long-term equilibrium relationship between resource biased technological progress, resource price and resource efficiency. resource biased technological progress has a short-term negative and long-term positive impact on resource efficiency, and resource price has a short-term negative and long-term positive impact on resource efficiency. Based on this, this paper puts forward relevant policy recommendations to promote the improvement of resource efficiency of mariculture.